TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI PULSA MENGGUNAKAN APLIKASI JUAL BELI PULSA ONLINE - Naufal Hilal Rofi; Irvan Iswandi; Muhammad N. Abdurrazaq (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The more people owning handphone makes credit needs getting increase too. This makes many people take credit commerce as their business. Some make it as their main job and establishing a counter, and some make it only as side hustle to get additional income by selling credit. This research aimed to find out how was Islamic Law Review on the transaction of Online Credit Commerce Using Online Credit Commerce Application. Through the problem mentioned above then the specific purpose of this research was to find out the transaction mechanism of credit commerce using online credit commerce application and to find out Islamic law review on the transaction of credit commerce using online credit commerce application. This research employed qualitative research method. The data used were primary data. The data collection was conducted by using documentation and interview method. The source of primary data in this research was informant who owned credit commerce business using online credit commerce application. Related to the secondary data used were in the form of documents, books, notes, and so on. The results of this research showed that credit commerce transaction using online credit commerce application is the same with credit commerce in general. Only the media is different namely in the form of online credit commerce application. And reviewed from Islamic law, credit commerce using online credit commerce application is considered legal because it has been in line with the principles and requirements of commerce in Islamic shariah law and does not contain something which disadvantages either the seller or the buyer.